Effects of Rosuvastatin and Pitavastatin on Ischemia-Induced Myocardial Stunning in Dogs - Kumi Satoh; Akira Takaguri; Mai Itagaki; Seiichiro Kano; Kazuo Ichihara (Elsevier, 2008)
Incomplete recovery of myocardial contraction after reperfusion following brief ischemia is called the "stunning phenomenon" in an animal experiment. A hydrophilic 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor (statin) does not affect this phenomenon, but lipophilic statins further reduce the contraction during reperfusion. The effects of novel hydrophilic rosuvastatin and lipophilic pitavastatin on myocardial stunning in dogs were examined. In a preliminary experiment in vitro, pitavastatin reduced L6 cell viability at 10−6M and higher, whereas rosuvastatin and pravastatin up to 10−5M did not show such effects. An empty capsule or a capsule filled with rosuvastatin (2 mg/kg per day) or pitavastatin (0.4 mg/kg per day) was orally administered to dogs. After 3 weeks, both statins lowered the serum cholesterol level to the same extent. Under pentobarbital anesthesia, dogs were subjected to 15-min ischemia followed by 120-min reperfusion. Ischemia arrested the myocardial contraction in the ischemic area, and reperfusion recovered it but incompletely, showing the stunning phenomenon. Rosuvastatin did not modify the stunning phenomenon, while pitavastatin further deteriorated the myocardial contraction during reperfusion. Keywords:: 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, heart, coronary artery, ischemia, ATP